A representação do salazarismo em Afirma Pereira, de Antonio Tabucchi - Pereira, Marcos Vinicius Biagi [UNESP] (2015)
This study aimed to study the relationship between history and literature in the representation of Salazar in Antonio Tabucchi's Afirma Pereira. The analysis of the work started by some reflections on the origin of the novel and its features, from Bakhtin and Lukács studies. Following, deepen aspects of the relationship between literature and history, that guided our look at the issue of fictional representation proposed by Tabucchi, by differentiating between fictional narrative and historiographical narrative. This relationship raises issues for the classic historical novel, as the contemporary. So we analyzed some traits of both variations of this novel form, establishing how the historical novel is updated second Jameson and Anderson. Then we entered a historical approach about Salazar to understand how salazarismo is subverted by Tabucchi in his fictional construction. Based on the theory of mitos ideológicos do Estado Novo, of the portuguese historian Fernando Rosas, in the aspects of the novel and the historical novel, form the theoretical foundation for the analysis of the work studied here. We seek to establish how the tabucchian historical novel questions salazarism and european totalitarianism and the author of which devices for such construction, for example, the subversion of mitos ideológicos do Estado Novo by some characters. Indeed, as a result of research we can establish that the work is a contemporary historical novel updating and transforming the historical novel concept, and the fictional representation of Salazar is made through questioning look that reverses the salazarism main bases and exposes them like some way of reflection about that period.